Heavy metal distribution and ecological risk in surface sediments of the Bohai Sea - Shilin Li; Jianlei Chen; Xuzhi Zhang; Jianshe Zhang; Yongjiang Xu; Yong Xu (PLoS ONE, 2025)
Heavy metal contamination in marine sediments poses significant ecological risks, particularly in semi-enclosed seas like the Bohai Sea, where limited water exchange exacerbates pollution retention. Heavy metals are persistent, bioaccumulative, and toxic, making their assessment crucial for environmental management. This study investigated the spatial distribution, seasonal dynamics, and potential ecological risks of heavy metal contamination in the central Bohai Sea, with an emphasis on regulatory interventions and anthropogenic influences. The annual average concentrations of Cu, Zn, Pb, Cd, Hg and As in surface sediments were 15.951, 32.556, 15.234, 0.250, 0.028 and 2.628 mg/kg, respectively, all below China’s Class I Marine Sediment Quality Standards. Seasonal variations revealed peak concentrations in August for Zn, Pb, Hg and As, likely driven by increased terrestrial inputs and hydrodynamic conditions. Cd exhibited the highest ecological risk, with a single-factor risk index exceeding 30 in May, followed by Hg, Pb, Cu, As and Zn. The comprehensive pollution index remained below 5 across all seasons, indicating overall low pollution levels. However, localized exceedances of Class I standards for Cu, Pb and Cd were observed, particularly in summer and autumn. Spatially, metal concentrations were higher near industrial and riverine discharge zones, with anthropogenic sources such as petrochemical industries, aquaculture, and urban runoff contributing significantly. This study highlighted seasonal and spatial heterogeneity in heavy metal contamination in the central Bohai Sea, emphasizing the influence of industrial activities and hydrodynamic processes. While overall pollution levels were low, the high ecological risk associated with Cd underscores the need for continued monitoring and targeted pollution control measures. Strengthening enforcement of industrial regulations, improving sediment management, and addressing seasonal fluctuations in pollutant inputs were critical for mitigating future risks. These findings provided a scientific foundation for sustainable marine environmental management and policy formulation in the Bohai Sea.